Meningkatkan Kinerja Tenaga Medis UGD: Analisis Peran Kompetensi dan Disiplin Kerja - Ida Nirwana; Rasidah Nasrah; Zikra Ahmad Fachry (Lembaga Pengembangan Kinerja Dosen, 2025)
This investigation was conducted in the ER at M Natsir Hospital, Solok City. The goal of this research was to find out how substantial the impact of Competency and Work Discipline is on the Performance of ER medical workers at M Natsir Hospital, Solok City. Forty emergency medical staff from M Natsir Hospital in Solok City made up the study's population. The Total sample approach was the sample strategy employed. Questionnaires were employed in the data collection method. The performance of medical staff (Y) is influenced by the Competency (X1) and Work Discipline (X2) variables, according to multiple regression analysis. Y = 8.259 + 0.904 X1 + 0.125 is the multiple linear regression equation that was produced. The variables Competency (X1) and Work Discipline (X2) show significance according to the t-test